Modeling and Simulation of the Effectiveness of Patchwork Sandal Production Using Bpmn at Umkm Handycraft Sidoarjo: Pemodelan Dan Simulasi Efektivitas Produksi Sandal Kain Perca Menggunakan Bpmn Pada Umkm Handycraft Sidoarjo - Lailia, Mairatul; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
This study aims to improve the production process efficiency at UMKM Handycraft Rahayu Art, which specializes in making patchwork sandals in Sidoarjo. Through the BPMN (Business Process Modeling and Notation) approach, this research explores problem identification, business process modeling, and simulation to design effective improvements. Through field observations and interviews with stakeholders, the main problems in the production process were identified, including delays in the delivery of raw materials and inefficiencies in the workflow. Modeling and simulation steps were then taken to gain an in-depth understanding of the business process and propose improvement solutions. The modeling results showed an increase in throughput efficiency from 63.48% to 88.71% in scenario 1 and 86.73% in scenario 2. Additionally, the minimum process time was significantly reduced from 24 days 4 hours 10 minutes to 19 days 10 hours in scenario 1 and 15 days 44 minutes in scenario 2.